(untitled) - Neefjes, Koos (London, 2000)
This book offers an analysis of "the environment" in its broadest sense, one that includes both people and social relationships. It begins by reflecting on the relationships between poverty and environmental change, from both a theoretical and a practical perspective. It then presents frameworks for action by development agencies, exploring power relationships and ideas of stakeholder participation, and in particular the notion of sustainable livelihoods. It moves on to discuss practical tools and approaches to project management, and ends by considering how strategies and policies can address the structural causes of environmental degradation and poverty. The book is based on Oxfam's extensive experience of working in rural and urban contexts in the developing world. It can be used to support campaigning and lobbying, to improve the formulation and implementation of development strategies, and to strengthen participatory project planning
Keywords: Economics,Economics & economic theory,Kinh tế học,Học thuyết kinh tế và kinh tế học; Geography,Geography,Địa lý học,Địa lý học